Monkeying in the Middle| The Role of the Principal Supervisor - Janovitz, Jennifer Beth (University of Pennsylvania, 2018)
In large school districts, principal supervisors oversee groups of principals. Principal supervisors commonly have titles such as Area or Regional Superintendents, Leadership Directors or Network Leaders. They are situated in the organizational hierarchy between top district leaders (Chief-level positions) and principals, and serve as the link between these two groups. To reflect recent changes in the responsibilities of principals from a focus on school management to a focus on instruction, many school districts have re-conceptualized the role of principal supervisors based on the premise that having principal supervisors provide support to principals about issues that directly relate to teaching and learning is necessary in order to raise school performance. Using qualitative methods, this research study analyzed the role of principal supervisors as middle managers who are expected to develop the instructional capacity of the principals they supervise by examining how the organizational conditions of school districts and the practices of top district leaders and principals influence principal supervisors’ work. Since there is minimal scholarship in the field of education, the conceptual framework of the study draws on theoretical perspectives about middle managers and strategy implementation from the fields of business and organizational behavior—Argyris & Schon’s (1974) theories of action and Guth & MacMillan’s (1986) middle management expectancy theory. Through written questionnaires and interviews with top district leaders, principal supervisors and principals in a large, urban school district, this research found that principal supervisors do not spend the majority of their time focusing on developing the instructional capacity of the principals they supervise. Rather, as a result of principal supervisors’ positioning in the district’s organizational hierarchy, the organizational conditions and practices of top district leaders and principals, and principal supervisors’ views about their intended job functions, principal supervisors often serve as “brokers”—intermediaries between central office staff members and principals. Honig & Copland (2008) set forth the conceptualization of principal supervisors as “brokers,” and the findings from this study confirm their findings. However, the results of this study extend their research by offering numerous additional ways in which principal supervisors’ brokering serves central office staff members and principals. As a contribution to the existing scholarship about principal supervisors, I further distill Honig & Copland’s (2008) denotation of principal supervisors as brokers by dividing principal supervisors’ broader brokering functions into three more refined categories of buffering, bolstering and bridging, and providing evidence to support these distinctions. I contend that most of these brokering activities are consistent with the district goal of having principal supervisors support principals’ instructional leadership. The findings from this study have a variety of implications for school districts, including the need for districts to either further refine the role of principal supervisors based on the realities of principal supervisors’ daily work, or to address district organizational conditions and practices in a way that allows principal supervisors to serve their intended instructional role.